2013
DOI: 10.1371/journal.pntd.0002511
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Epidemiology of Mokola Virus

Abstract: Mokola virus (MOKV) appears to be exclusive to Africa. Although the first isolates were from Nigeria and other Congo basin countries, all reports over the past 20 years have been from southern Africa. Previous phylogenetic studies analyzed few isolates or used partial gene sequence for analysis since limited sequence information is available for MOKV and the isolates were distributed among various laboratories. The complete nucleoprotein, phosphoprotein, matrix and glycoprotein genes of 18 MOKV isolates in var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 65 publications
3
29
0
2
Order By: Relevance
“…The 0% prevalence of Mokola virus recorded in shrews in this study agrees with Kantakamalakul who investigated five hundred rodents and shrews for rabies virus using direct immunoflorescnce and reported 0% prevalence [47]. Kgaladi et al after his survey on Moklola virus reported that although, the first isolates of Mokola virus were from Nigeria and other Congo basin countries, all reports over the past 20 years have been from Southern Africa [27].…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The 0% prevalence of Mokola virus recorded in shrews in this study agrees with Kantakamalakul who investigated five hundred rodents and shrews for rabies virus using direct immunoflorescnce and reported 0% prevalence [47]. Kgaladi et al after his survey on Moklola virus reported that although, the first isolates of Mokola virus were from Nigeria and other Congo basin countries, all reports over the past 20 years have been from Southern Africa [27].…”
Section: Resultssupporting
confidence: 88%
“…The human cases of Mokola virus infection have demonstrated its zoonotic potential [16,26] but a natural reservoir is yet to be identified [27]. The fact that all cases of Mokola virus infection in South Africa, as well as all but one from domestic animals from other countries in Africa [28][29][30][31] have been confined to cats, strongly suggests that the reservoir is to be found among their prey (shrews and rodents) as the virus has been isolated from them [15,[32][33][34].…”
Section: Journal Of V Journal Of Veterinary Science and Eterinary Scienmentioning
confidence: 99%
“…To elucidate whether the induction of disease in these vaccine-induced rabies cases was a result of mutations at known antigenic sites [19][20][21][22][23][24][25][26][27][28][29][30][31][32], all sequences were screened for nucleotide exchanges at the respective genome positions. The analysis revealed no nucleotide exchanges between the SAD Bern orig -derived vaccine virus strains and their induced rabies cases in any of the known antigenic sites, including SNVs on these particular positions.…”
Section: Known Antigenic Sites Are Rarely Affected By Amino Acid Exchmentioning
confidence: 99%
“…Furthermore, SARS coronavirus (SARS‐CoV) has been identified in Chinese bats, and it has been shown that the SARS‐CoV genome sequence generated from humans and civets during the 2002–2003 outbreak in China phylogenetically clustered within the bat associated group of SARS‐CoV‐like viruses (Calisher et al., ; Drexler et al., ; Moratelli & Calisher, ; Wong et al., ). Filoviruses, including Ebola and Marburg viruses, also pose a significant threat to human health, and despite human outbreaks being rare and sporadic, they are associated with a high case fatality rate (Hoffmann et al., ; Jayme et al., ; Kgaladi et al., ; Plowright et al., ).…”
Section: Introductionmentioning
confidence: 99%